PENGARUH INSENTIF DAN PEMASARAN DIGITAL TERHADAP PRODUKTIVITAS KERJA KARYAWAN PADA ERA PANDEMI COVID-19 DI PERUSAHAAN MASTER CASH AND KREDIT - Diana Harahap; Elida Florentina Sinaga Simanjorang; Mulya Rafika (Bajang Institute, 2022)
In the midst of the Covid-19 pandemic, the Master Cash and Credit company took a number of steps to keep the company's business growth healthy. This study uses a quantitative approach to determine the effect of incentives and digital marketing on employee work productivity in the era of the Covid-19 pandemic in Master Cash and Credit companies. The results showed that the variables of incentives and digital marketing had a positive and significant effect. This can be seen from the calculated t value of each incentive-free variable of 3,274 and digital marketing of 2,441 greater than the table t value of 1,682. Then simultaneously also obtained the result of calculating F = 9.104 greater than the value of F table = 2.83 so that it can be concluded that independent variables have a positive and significant effect on employee work productivity.